CEO mandate and age in the comparability of financial statements - Sousa, Allison Manoel de (2022)
The present study analyses the influence of mandate time and Chief Executive Officer (CEO) age on comparability in Brazilian market publicly traded companies. In a yearly basis, 58 companies were analyzed from 2013 to 2019. Data were submitted to panel data regression which indicated mandate influences comparability in a positive way. It was also found that CEO age does not exert a direct influence on comparability although it is a personal characteristic acting indirectly as a moderator factor in the relation between mandate and comparability. Younger CEOs tend to decrease comparability of accounting information during their mandate. The study is important since it demonstrates that changes on accounting choices are more aggressive in the beginning and slow down as mandate increases. Another important aspect, in practical field, refers to the evidence that CEO age potentiates mandate influence on comparability.